Exhausted Senses: Between the Eye and the Ear in 'Long Observation of the Ray' and 'The Voice/Verbatim'. Issue 2 (September 2022) - Moore, Brian Michael
Abstract : Between October 1975 and November 1976, Samuel Beckett began, revised and abandoned a manuscript for a prose piece entitled 'Long Observation of the Ray' (at least) twice. After a period of writing for television, Beckett's next foray into prose resulted in 'The Voice/Verbatim', a text that – due to its partial incorporation into Company  – resists definition as either draft or abandoned work. This article parses Beckett's motivations for abandoning (and reabandoning) these pieces and demonstrates that the 'ray' and the 'voice' partake in a broader conversation in Beckett's work concerning the visual and the audible. The 1970s, a time of unprecedented modulation between media in Beckett's writing, see Beckett almost capriciously tailoring images to fit media, or vice versa. His writing desk between 1975 and 1977 was home to 'ends and odds' in various media: two stage plays, two TV plays, a litany of poems and prose. Focusing on the writing that immediately preceded his first attempt at 'Long Observation', the works that come between its first and second abandonment, and the inception of Beckett's late prose 'trilogy', this article argues that one can witness a negotiation between writing the 'eye' and the 'ear' as he wrangles with how to put the observations of the 'ray' and the overheard 'voice' in words. This article contextualises this dynamic within discourses surrounding modernism and the senses, philosophical responses to 'ocularcentrism' and the ways in which manuscript research can harmonize with Deleuze's reading of Beckett's 'exhaustive' language. Alongside this, investigations into Beckett's late allusions to Dante's description of Virgil's hoarse voice or faint appearance and W. B. Yeats's 'deepening shades' reveal this compositional struggle seeping into (or deriving from) Beckett's reading habits; traversing the 'ill-heard' and the 'ill-seen', these references encapsulate Beckett's ongoing struggle to isolate in words the senses of sight and hearing.